2022
DOI: 10.3390/ijms23073695
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis, Functions, Interactions, and Resources of Non-Coding RNAs in Plants

Abstract: Plant transcriptomes encompass a large number of functional non-coding RNAs (ncRNAs), only some of which have protein-coding capacity. Since their initial discovery, ncRNAs have been classified into two broad categories based on their biogenesis and mechanisms of action, housekeeping ncRNAs and regulatory ncRNAs. With advances in RNA sequencing technology and computational methods, bioinformatics resources continue to emerge and update rapidly, including workflow for in silico ncRNA analysis, up-to-date platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 250 publications
(198 reference statements)
0
10
0
Order By: Relevance
“…As reviewed by Chao et al [18], the biogenesis of miRNAs is a multi-step procedure which involves transcription, processing, alterations, and then RNA-induced silencing (RISC) complex assembly. First, a pri-miRNA (primary miRNA) is transcribed from RNA Polymerase II containing a hairpin RNA secondary structure.…”
Section: Genesis Of Non-coding Rnas and Classificationmentioning
confidence: 99%
“…As reviewed by Chao et al [18], the biogenesis of miRNAs is a multi-step procedure which involves transcription, processing, alterations, and then RNA-induced silencing (RISC) complex assembly. First, a pri-miRNA (primary miRNA) is transcribed from RNA Polymerase II containing a hairpin RNA secondary structure.…”
Section: Genesis Of Non-coding Rnas and Classificationmentioning
confidence: 99%
“…These RNAs are mostly transcribed in the nucleus with RNA polymerase II in an mRNA-like way. The mechanisms by which plant lncRNAs function are numerous, and some of them are better understood in animals [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Recent studies have shown that the short open reading frames (sORFs) of some plant lncRNAs encode functional small peptides (micropeptides) with a size of around 5 to 100 amino acids [ 10 , 12 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…(1) In addition to performing a direct role as a miRNA precursor, lncRNA can be spliced into shorter miRNA. For example, MiR869a and miR160c may be spliced into lncRNAs npc521 and npc83 [ 6 ]. (2) lncRNA can be cleaved by miRNA as a target [ 7 ].…”
Section: Introductionmentioning
confidence: 99%